Deutsche Bahn: Rail Network Monopoly, Financial Locusts and the State - Thomas Ehrmann; Aloys Prinz (Wirtschaftsdienst)
Abstract Deutsche Bahn had to pay a total dividend of 2.85 billion euro over the past six years with cumulated annual results of just under 2.35 billion euro. During that time period, DB Netz AG pursued a monopolistic pricing policy for the transport companies on downstream competitive markets, which had serious consequences for both DB’s own companies and its competing transport companies. This article explains why the company was economically forced to use the strategies that it did. It then outlines what the shareholder should do to achieve the goals set out in the coalition agreement. This agreement states the aim is “the increase in the market share of the railways”, whereby “the focus is not on maximizing the profit, but on sensibly maximising the traffic on the railways”. In economic terms, this means that the transport output by rail should be maximised instead of profits.